Impact of COVID-19 among people who use drugs: A qualitative study with harm reduction workers and people who use drugs - Fiona N. Conway; Jake Samora; Katlyn Brinkley; Haelim Jeong; Nina Clinton; Kasey R. Claborn (BMC, 2022)
Abstract Background Fatal drug overdoses in the USA hit historical records during the COVID-19 pandemic. Throughout the pandemic, people who used drugs had greater odds of contracting COVID-19, increased drug use due to COVID-related stress, and heightened levels of anxiety and depression. This qualitative study examined the specific ways the pandemic negatively impacted people who use drugs. Methods Qualitative interviews with 24 people who use drugs and 20 substance use harm reduction workers were conducted. Data from the qualitative interviews were analyzed using applied thematic analysis to identify emergent themes based on the a priori research goals. Results Thematic analysis identified several common experiences during the pandemic among people who use drugs. These included mental distress due to financial strain and social isolation; increased drug use; increased risky drug-seeking and use behaviors due to changes in the drug markets; and reduced access to harm reduction, treatment, and recovery support services. Conclusions Our study highlighted critical systemic failures that contributed to the rise in overdose deaths during the COVID-19 pandemic. Addressing these challenges through policy reform and improved funding models will ensure the sustainability of harm reduction services and increase access to substance use treatment among highly vulnerable people who use drugs.